The Effect Of Course Review Horray Learning Assisted By Human Apron Media On Science Learning Outcomes - Fadilah Hasti Cahyaningtyas; Ari Suryawan; Dhuta Sukmarani (Prosiding University Research Colloquium, 2021)
This study to determine the effect of the effect of Course Review Horray learningassisted by human apron media on science learning oitcomes research on 5th elementarygrade students in kradenan village. This type of pre-experimental research with the designof one group protest posts.Course Review Horray learning with human aprons media on science learningoutcomes in fiifth grade elementary school students in Kradenan village totaling 18students.The data collection method used in this research is using the pretest and posttesttest methods in the form of multiple choice questions. The sampling technique used totalsampling. Data was collected through wal pretest posttest and than analyzed using unWilcoxon in the SPSS 25.00 program for windows.The results showed that the learning Course Review Horray assisted by human themecermatusia apron media had an effect on the learning outcomes of natural science. Thisis evidenced from the results of the analysis of the Wilcoxon signed rank test test with theAsymp value. Sig. (2-tailed) is 0,000 <0.05 and Z score is -3,728. Based on the result of theanalysis and discussion, there is a difference in the average score pretest and posttest,namely the results pretest 54,97 and posttest 78,96, both of which have a difference of 20%.The results of the study can be concluded that learning Course Review Horray assisted byhuman apron media has an effect on learning outcomes of natural science learning in 5thgrade students of Kradenan Village, Srumbung District, Magelang Regency.